Бездротова передача медико-біологічних даних - Єрошенко, О. А.; Прасол, І. В. (My University, 2020)
Discusses the organization of a wireless system for collecting biomedical information, which is intended for use in everyday life of a person in order to control the main parameters of life.
Keywords: ZigBee; Wi-Fi; Bluetooth; дротова мережа і бездротова